Exploring Intertidal Stone Elements at ȾEL ̧IȽĆE/ c̓əl̓íɫč - Hooton, Rachel (2022)
W̱SÁNEĆ and lək̓ʷəŋən First Nations territories span throughout the southern part of Vancouver Island, where their connection to space and place has never diminished. Significant places throughout the landscape of their territories have been sustained and managed by their families since time immemorial. This project aims to support the work of Dr. Brian Thom and the W̱SÁNEĆ First Nations in recognizing ancient intertidal stone elements at ȾEL ̧IȽĆE / c̓əl̓íɫc (Cordova Bay, Victoria, British Columbia) as part of an integrated sea garden. Although the South Saanich Treaty of 1852 resulted in the movement of lək̓ʷəŋən and W̱SÁNEĆ ancestors to new locations, the living remnants of their fishing technologies and lasting legacy on the land is still present. Through the lens of sociocultural anthropology and archaeology, this project aims to substantiate the physical remains of intertidal stone elements and their connection to lək̓ʷəŋən and W̱SÁNEĆ sea garden and fishing technologies. Undergraduate Reviewed